NILAI-NILAI ILAHIYAT DALAM PENDIDIKAN SEBAGAI SYARAT PEMBENTUKAN KEPRIBADIAN MUSLIM - Hoirun Nisa (JURNAL PUSAKA, 2016)
Education which is derived from revelation of Allah and sunnah of Prophet Muhammad becomes the main component in moslem's character building. Human is created with four potential abilities such as; instinct, sense, mind and religion. These potential abilities are used by human beings to equip themselves as the khalifah (the caliph) in the earth. Through education, human potential abilities must be developed and actualized well because human beings are bound with their values, duties, and responsibilities. The religious values are always corresponded with human's natural tendency so that becomes the basis in designing Islamic education sistem wich is implemented in formal and informal education, especially in the family. Religious values must be included in education goal, curriculum, media, and process which is still continuing up to now. The implication of the education which is full of religious values is human beings can do their Jobs and their responsibilities as the caliph. In conclusion, it can be said that human beings who have religious values can be called as truly moslems. Keywords: religious values, education, moslem's character